A case control study on autopsy findings in sudden unexplained nocturnal death syndrome. Issue 1 (31st January 2014) - Gervacio, G; Lim, M; Reganit, P; Encinas, M; Macapugay, L; Palmero, J; Nierras, C; De los Reyes, C; Geronimo, F
Abstract : Aim: Sudden unexplained nocturnal death syndrome (SUNDS) has been linked to the Brugada syndrome. In some places, acute haemorrhagic pancreatitis is widely held to cause it. We conducted a systematic, controlled autopsy study on Filipino SUNDS victims to rule out structural heart findings as well as acute haemorrhagic pancreatitis as causes. Methods and results: A case control autopsy study was conducted comparing SUNDS victims between 18 and 50 years of age who died within 1 h of symptom onset with age- and gender-matched controls. There were 24 SUNDS (mean age 34.5 years) and 24 controls (mean 32.7 years). The autopsy incidence of structural heart disease was 8.3% (95% CI (1% to 27%)) and focal pancreatic haemorrhage was 4.17% (95% CI (0.1% to 20%)) but zero for true acute haemorrhagic pancreatitis among SUNDS victims. Autopsy findings in SUNDS versus controls were not significantly different from each other, showing no diagnostic abnormality in any of the organs. There was no significant difference in the incidence of acute haemorrhagic pancreatitis in both the SUNDS and control groups. We did not find fetal dispersion of the atrioventricular (AV) node, sclerosis or fibrosis of the AV conduction system, in a substudy of SUNDS cases. Conclusions: We have shown that there is no significant difference in the overall autopsy findings between SUNDS and controls. Autopsy findings were normal in 70% of SUNDS; no cardiac structural pathology was found in 87% of cases. Haemorrhagic pancreatitis is the cause of death in a minority of SUNDS. The cardiac conduction system is normal in a subgroup of SUNDS studied.